2017
DOI: 10.1177/0022042617743775
|View full text |Cite
|
Sign up to set email alerts
|

Medical Marijuana and Crime: Substance Use and Criminal Behaviors in a Sample of Arrestees

Abstract: After decades of prohibition, laws allowing marijuana use for medical and, in some cases, recreational purposes have been enacted across the country. To date, however, little is known about medical marijuana use, particularly regarding its relationship to criminal offending and use by nonauthorized persons. The current study bridges this gap by examining offending patterns in a sample of recent arrestees in Maricopa County, Arizona, identified and interviewed through the Arizona Arrestee Reporting Information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The age range of the arrestees with drug-related crimes was 30-33 years. Considering the demographic characteristics of the arrestees, our participants were as young as the samples studied in other relevant studies, such as in French [17,18], American [19], Chinese [20], and English [21] arrestees. Generally, being young and unemployed can increase the risk of being arrested [22].…”
Section: Discussionmentioning
confidence: 99%
“…The age range of the arrestees with drug-related crimes was 30-33 years. Considering the demographic characteristics of the arrestees, our participants were as young as the samples studied in other relevant studies, such as in French [17,18], American [19], Chinese [20], and English [21] arrestees. Generally, being young and unemployed can increase the risk of being arrested [22].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we acknowledge that the costbenefit analysis did not measure all the possible detriments of recreational legalization. Adverse costs of recreational legalization were limited to crime increases, but there are other potentially adverse effects that could have occurred, such as users becoming more likely to drive under the influence (Cheon, Decker, & Katz, 2018) or increased access for underage users. However, given the large CBR values observed for sales revenue, the adverse effects would have to be quite large to offset the benefits given that sales continue to increase in Denver.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of self-reported data has been demonstrated repeatedly in prior criminological studies. Prior research suggests more than 80% convergence between self-reported offending and official reports of arrest (Bersani & Piquero, 2017; Piquero et al, 2014) and has reported a strong and robust relationship between self-reported drug use and urinalyses tests of illicit drugs (Cheon et al, 2018). The distributions of the outcome measures in the sample are given in Table 2 below.…”
Section: Background Of the Studied Case: Juvenile Delinquency Risk Asmentioning
confidence: 99%